(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The intellectual community is seriously sceptical about the direction that our society is taking. Prospective teachers undergoing teacher education become the citizens who will shape our society and make contributions as educators too. Because teacher education significantly enhances prospective teachers’ skill development, it has a critical potential to impact our society’s future. This paper focuses on the significance of life skill-based education in improving the quality of teacher education programme. The researcher has explored the status of life skill development in 256 prospective teachers through an online form derived from the life skill assessment scale developed by Pearson and Kennedy. The life skills approach emphasises more than just knowledge acquisition. Through the use of life skills, students and teachers can better understand and know themselves, live more purposefully and consciously, find personal fulfilment, and meet both their academic and personal objectives.